'A torn shoulder': An emergency department case study. (March 2016) - Gibbons, Lynda
Highlights: Proximal biceps tendon injuries are poorly documented in nursing literature. A systematic approach to patient assessment is illustrated. This paper will increase awareness of proximal biceps tendon injuries. Abstract: Background: Rupture of the biceps is not a very common presentation to the emergency departments; as a result, it is poorly documented, especially in nursing literature. It is important that these patients are appropriately managed by registered advanced nurse practitioners. As the diagnosis of rupture is usually made on clinical grounds with imaging assisting in the diagnosis, left untreated these injuries can lead to considerable functional deficits. Methods: The following paper is a case study based on a patient who presented to the emergency department with a proximal biceps rupture following trauma. The paper focuses on the clinical assessment and management of patients who present to the emergency department with these injuries. Results: This case study increases awareness of bicep ruptures and its management in the ED. Discussion points include the neurovascular assessment of these patients, the appropriateness of diagnostic imaging, and in-depth clinical examination techniques. Conclusion: Rupture of the biceps tendon is often a result of a sudden forceful extension of the elbow against a previously contracted biceps and flexed elbow. The patient often describes a popping noise and presents with a 'popeye' deformity over their biceps. It is important to be vigilant with these injuries as early recognition will optimise the patients' outcomes.